Perceived School Culture and Teachers’ Job Performance in Government Aided Secondary Schools in Sheema Municipality, Uganda - Nkwatsibwe, Innocent; Balimuttajjo, Sudi (Journal of Research Innovation and Implications in Education., 2024)
The purpose of the study was to explore the influence of perceived school culture on teachers’ job performance in government aided secondary schools in Sheema municipality, Uganda. The study was quantitative and adopted a crosssectional survey research design. A self-administered questionnaire was used to collect data from 252 respondents using census strategy. Descriptive statistics were used to analyze objectives 1 and 2. Pearson Correlation Coefficient was used to test the relationship between perceived school culture and teachers’ job performance. The study findings revealed that 77.4% of the teachers reported strong school culture and 22.6% reported moderate levels of school culture. It was revealed that 91.2% of teachers reported high levels of job performance while 8% reported moderate levels of job performance. The study established that positive significant relationship exists between perceived school culture and teachers’ job performance (r = .29, p ˂ .01). The findings agree with studies conducted by Bukhuni and Iravo (2015), Edelstein (2012) and Kamaroellah and Mubarak (2019). The study findings, however, disagree with Ghanney et al (2017). The study recommended that the ministry of education should come up with clear training programs for teachers to teach them about the vitality of upholding strong school cultures in their schools to boost job performance
Keywords: School culture; Job performance; Teachers; Secondary schools; Sheema Municipality; Uganda